The Role of Satisfaction With Job and Cognitive Trauma Processing in the Occurrence of Secondary Traumatic Stress Symptoms in Medical Providers Working With Trauma Victims - Gurowiec, Piotr Jerzy; Ogińska-Bulik, Nina; Michalska, Paulina; Kȩdra, Edyta; Skarbalienė, Aelita (Frontiers in Psychology, 2022)
Abstract Introduction: As an occupational group, medical providers working with trauma victims are prone to negative consequences of their work, particularly secondary traumatic stress (STS) symptoms. Various factors affect susceptibility to STS, including organizational and work-related factors, as well as individual differences. The aim of this study was to establish the mediating role of cognitive processing of trauma in the relationship between job satisfaction and STS symptoms among medical providers. Material and methods: Results were obtained from 419 medical providers working with trauma victims (201 paramedics and 218 nurses). Three standard evaluation tools, namely the Secondary Traumatic Stress Inventory, Work Satisfaction Scale, and Cognitive Trauma Processing Scale, were used in the study, as well as a survey developed for this research. Correlational and mediation analyses were applied to assess relations between variables. Results: The results showed significant links between STS symptoms and both job satisfaction and cognitive processing of trauma. Three cognitive coping strategies play the intermediary role in the relationship between job satisfaction and STS symptoms. However, this role varies depending on preferred strategies. Conclusions: Paramedics and nurses are significantly exposed to the occurrence of STS. Therefore, it is important to include medical providers in the actions aiming at prevention and reduction of STS symptoms. Keywords: STS symptoms, job satisfaction, cognitive trauma processing, medical providers working with trauma victims.